The Words of Affectivity. Affect, Category, and Social Evaluation Norms for 400 Polish Adjectives - Grzybowski, Szczepan J.; Wyczesany, Miroslaw; Cichecka, Hanna; Tokarska, Aleksandra (Frontiers in Psychology, 2021)
Emotional adjectives can be grouped into two main categories: denoting and connoting stable (personality) traits and denoting and connoting transient (mood) states. As such, they relate closely to the concept of affectivity, which is a pervasive tendency to experience moods of positive or negative valence. They constitute a rich study material for personality and affect psychology and neuroscience. The study was designed to establish a normed list of emotional adjectives with ratings encompassing 4 dimensions: emotional valence (positive, negative), emotional arousal (low-arousing, high-arousing), category (state, trait, hybrid) and social judgement (competence, morality, mixed). The adjectives were preselected on the basis of previous broad Polish norming studies, personality and mood questionnaires and a dictionary study. One hundred and ninety-five participants rated 400 adjectives that were chosen on the basis of similar linguistic variables (frequency, word length). The dataset measures were proven to be stable and reliable. Correlations between emotional valence and state-trait, valence and competence-morality and emotional arousal and competence-morality dimensions were found. The study was successful in preparing a dataset of well categorized (state, trait, hybrid) positive and negative adjectives of moderate to high arousal rating. Since the words were matched on linguistic variables, the set provides useful material that can be readily used for research into the effects of category and emotional dimensions on language processing, and as basis for new personality questionnaires and mood checklists. The dataset could also be seen as a supplement for broader sets of published normed materials in Polish that linked emotion and language.